PENGARUH HEDONIC SHOPPING TERHADAP PEMBELIAN IMPULSIF PADA RITEL MODERN (Studi Kasus pada Pelanggan Swalayan Gelael, Candi Semarang) - Ahmad Areadi; Wahyu Hidayat (Universitas Diponegoro, 2016)
The ability to know the characteristics of the customer is key in planning a marketing strategy of acompany retail business Gelael Supermarket. This type of research is explanatory research. Thepopulation of this research are all consumers / customers who shopped at Supermarket Gelael andthe sample of 99 people who are determined using the formula slovin. The sampling techniqueused purposive sampling non-probality means that sample with a certain considerations.Collecting data using the interview technique with the help of a questionnaire instrument with aLikert scale of measurement. Data were analyzed using correlation test, test the coefficient ofdetermination, and regression testing, as well as the significance test with the help of a computerprogram SPSS 20.0. Based on the research results, the variable hedonic shopping positive andsignificant effect on the variable impulse purchases with t count> t-table (5.504> 1.9847). Thecorrelation figure of 0,488 that is medium value. The advice can be given in this study is a modernretail company should further improve the quality and service that is able to create a sense of funfor consumers because it is a Gelael Supermarkets ability in reading factors - factors thatcontributed to the hedonic properties of the consumers themselves.